Social Learning Theory and the training of retail loss prevention officers. Issue 4 (October 2017) - Floridia, Ronald; Hollinger, Richard
Abstract This study investigated how retail loss prevention training practices and techniques influence the behavior and performance of loss prevention officers. Thirty semi-structured interviews were conducted with loss prevention officers from two major retailers located within the United States. The purpose of the interviews was to examine how specific elements of Social Learning Theory guided or informed loss prevention officer behavior. The results suggest that peer-trainers have the greatest influence on an officer's decision to conform or deviate from their company policy. From this data, evidence-based practices can be developed for retailers to avoid costly litigation stemming from inappropriate officer behavior.